Model based analysis of signaling pathways - Śmieja, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
The paper is concerned with application of mathematical modeling to the analysis of signaling pathways. Two issues, deterministic modeling of gene transcription and model-driven discovery of regulatory elements, are dealt with. First, the biological background is given and the importance of the stochastic nature of biological processes is addressed. The assumptions underlying deterministic modeling are presented. Special emphasis is put on describing gene transcription.
Keywords: signaling pathways; dynamical systems; systems biology; interferon-beta